2022
DOI: 10.2196/37234
|View full text |Cite
|
Sign up to set email alerts
|

Behavior Change Techniques in Digital Health Interventions for Midlife Women: Systematic Review

Abstract: Background Digital health interventions are efficacious in health-promoting behaviors (eg, healthy eating and regular physical activity) that mitigate health risks and menopausal symptoms in midlife. However, integrated evidence-based knowledge about the mechanisms of change in these interventions is unclear. Objective This systematic review aimed to evaluate studies on behavior change techniques (BCTs) and mechanisms of change in digital health interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 107 publications
1
4
0
Order By: Relevance
“…“Self-monitoring,” “biofeedback,” and “goal setting of PA behaviour” were the most frequently used BCTs across the included studies. These findings concur with previous literature on digital behavior change interventions targeting PA, which also highlighted the role of “social support” in adults [ 103 - 105 ] and older adults [ 106 ]. In this review, “social support” was used in 67% (6/9) of the studies targeting both healthy [ 56 , 76 , 79 , 85 ] and clinical (ie, survivors of breast cancer) [ 81 , 83 ] midlife women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…“Self-monitoring,” “biofeedback,” and “goal setting of PA behaviour” were the most frequently used BCTs across the included studies. These findings concur with previous literature on digital behavior change interventions targeting PA, which also highlighted the role of “social support” in adults [ 103 - 105 ] and older adults [ 106 ]. In this review, “social support” was used in 67% (6/9) of the studies targeting both healthy [ 56 , 76 , 79 , 85 ] and clinical (ie, survivors of breast cancer) [ 81 , 83 ] midlife women.…”
Section: Discussionsupporting
confidence: 91%
“…Reporting of interventions and mode of delivery in the included studies was insufficient; accordingly, we could not comment on the link between the described BCTs and mechanisms of action, a problem highlighted in similar reviews. Sediva et al [ 103 ] highlighted the relevant real concern of low treatment fidelity on the delivery of content as planned across the 13 included complex interventions, including PA apps. By contrast, without adequate information reported on measurements of fidelity or ensuring that the underpinning theory is reflected in the design and implementation process, implementation failure can potentially occur and, thus, the real-world effectiveness of such interventions must be considered with caution [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…AlSwayied et al [65] found early evidence that mobile-based physical activity programs are helpful for enhancing moderate to vigorous physical activities among midlife women. Another systematic review by Sediva et al [66] on 13 digital health interventions found that most interventions for midlife women targeted weight loss, lifestyles, and menopausal symptom management and primarily relied on the provision of instructions on healthy behaviors, fostering capability, and motivation. Although the heterogeneity of the studies and their outcomes forbids a conclusion about the general effectiveness of these digital health interventions, it is hoped that these contents may build confidence and familiarity in women with their health care providers, thus connecting women in need to more specialized support.…”
Section: Discussionmentioning
confidence: 99%
“…These behaviour changes can also be mapped to Michie’s behaviour change taxonomy [ 31 ]. Sediva et al [ 32 ] also highlight an opportunity for this in their systematic review on behaviour change techniques in digital health interventions for midlife women, indicating an overall weak use of theory, with an insufficient description of how specific behaviour change techniques were activated, low levels of treatment fidelity and insignificant outcomes.…”
Section: Discussionmentioning
confidence: 99%